Case‐based discussion supporting learning and practice in optometry. (26th August 2014) - Bullock, Alison; Barnes, Emma; Ryan, Barbara; Sheen, Nik
Abstract Purpose To enhance continuing professional development and address the risk that professional isolation poses, the UK General Optical Council introduced a requirement for all optometrists to engage in at least one case‐based discussion per 3 year cycle of continuing education. In this paper, we explore participants' impression of the acceptability, effectiveness and long‐term impact‐on‐practice of case‐based discussion as a mode of continuing education. Methods Case‐based discussion participants attended an evening session comprising a lecture and a group discussion. They completed three questionnaires: prior to the session, immediately post‐session and 3–4 months post‐session. We coded the questionnaires to allow matching. Results Seventy‐five case‐based discussion groups were held with 379 participants; 377 completed both pre‐ and post‐questionnaires and 331 (88%) returned a follow‐up questionnaire. Case‐based discussions were an acceptable method of learning, with many preferring it to distance‐learning. Prior to the event, women, employees and part‐time workers were more likely to have concerns about participating. In terms of learning, gaps in knowledge were more likely to be revealed in those who work in isolation. The respondents highlighted social aspects, reassurance of practice as well as new learning. Participants significantly improved self‐confidence ratings in all key learning areas. At three months post‐session, the majority (75%) self‐reported that they had implemented their intended changes to practice. Conclusions The evaluation showed that participants felt that case‐based discussion developed their knowledge, notably for sole practitioners, and influenced later workplace practice. The peer interaction of this mode of continuing education can combat professional isolation.